Boson peak and structural heterogeneity in ternary SiO2-Al2O3-B2O3 glasses - Ando, Mariana Fatobene; Fuhrmann, Sindy; Pan, Zhiwen; Rodrigues, Bruno Poletto; Mori, Tatsuya; Ebbinghaus, Stefan G.; Wondraczek, Katrin; Kitani, Suguru; Wondraczek, Lothar (Journal of the American Ceramic Society, 2021)
We use low-temperature heat capacity, low-frequency Raman scattering, and THz time domain spectroscopy in order to scale the vibrational density of states and the Boson peak in SiO2-Al2O3-B2O3 Yb-laser host glasses. When substituting B2O3 for SiO2 at constant Al2O3 dopant level, we find an optimal value for the ratio of B/Al in terms of mixture stability, at which the excess in the electron donor capability of Al2O3 (relative to the SiO2 backbone) is compensated by the more acidic B2O3. At this composition, Al2O3 plays a mediating role in the structure of aluminoborosilicate glasses, facilitating dissolution of Yb2O3 and admixture of B2O3 into the SiO2 network.
CRIS-Team Scopus Importer:2023-04-20
Keywords: glass; heterogeneity; optical fiber; silica; Yb-doping